The Purchased Patient Advocate - Elliott, Carl (The Hastings Center report, 2018)
Thirty years ago, the only people drug companies thought worth buying were doctors and politicians. But the ground began to shift in the 1980s, when HIV/AIDS activists showed everyone how powerful patient advocates could be. It didn't hurt that many advocates were so strapped for money that they could be purchased at bargain prices. Today over 80 percent of patient advocacy groups accept money from the pharmaceutical industry, and the testimony of marginalized patients carries such cultural power that drug companies like Sprout Pharmaceuticals are willing to fake grassroots patient movements. Whether you see this change as a victory for patients or a cautionary tale of institutional corruption depends on how deeply committed you are to the idea that free markets represent our best hope for the future of medicine. Count Sharon Batt as one of the skeptics. Her superb new book, Health Advocacy, Inc.: How Pharmaceutical Funding Changed the Breast Cancer Movement, is a deep scholarly account of the way that pharmaceutical funding has warped the patient advocacy movement into a tool for medical capitalism. Taking the Canadian breast cancer movement as a case study, Batt uses extensive interviews, scholarly resources, and her personal history to explore the struggles faced by patient advocates as they decide whether industry funding is necessary to keep their organizations afloat.